2005
DOI: 10.1063/1.2060950
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of bias-field-dependent dielectric properties in ferroelectric thin films

Abstract: The bias-field-dependent dielectricity of ferroelectric thin films is studied by use of a multilayer model capable of modeling saturated and unsaturated hysteresis behavior under arbitrary fields. The simulated minor hysteresis loops at different bias fields are used to calculate the variation of dielectric permittivity with the bias field. The -E loops show asymmetric shifting along the field axis when the film is assumed to possess a secondary dielectric layer with trapped charge. Simulated D-E and -E loops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Fatigue heterogeneity is defined as a variation in ferroelectric properties with spatial region during fatigue cycling. Measurement of hysteresis loops driven by a symmetric field may show the asymmetry of the macroscopic hysteretic behavior in fatigued ferroelectric samples. It has been reported that all parameters including polarization, coercive field, dielectric constant, and piezoelectric coefficient are spatially highly heterogeneous after cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue heterogeneity is defined as a variation in ferroelectric properties with spatial region during fatigue cycling. Measurement of hysteresis loops driven by a symmetric field may show the asymmetry of the macroscopic hysteretic behavior in fatigued ferroelectric samples. It has been reported that all parameters including polarization, coercive field, dielectric constant, and piezoelectric coefficient are spatially highly heterogeneous after cycling.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] The Preisach model is applied not only to the ferromagnetic system but also to ferroelectric D-E hysteresis, 19) compensation for the hysteresis of piezoelectric actuators, 20,21) piezoelectric nonlinearity, 22) and dielectric nonlinearity. 23) However, there are few reports on the Preisach modeling of strain butterfly hysteresis. Yang et al reported the Preisach modeling of the strain butterfly loop of ferroelectric films.…”
Section: Introductionmentioning
confidence: 99%